2014
DOI: 10.2337/db13-1689
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of MicroRNA 130a-3p in Hepatic Insulin Sensitivity and Liver Steatosis

Abstract: MicroRNAs (miRNAs) are endogenous, noncoding, short, single-stranded RNAs that are evolutionarily conserved and believed to play a role in controlling a variety of biological processes. The roles of miRNAs in insulin resistance and liver steatosis, however, are largely unknown. The objective of this study was to evaluate the roles of miR-130a in the regulation of insulin sensitivity and liver steatosis. In our current study, we observed that overexpression of miR-130a-3p increases insulin signaling in both Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 39 publications
0
53
0
Order By: Relevance
“…The effects of miR-130a-3p were first studied in mice and were later verified in studies with human embryonic stem cells. It appears to be a vertebrate-specific miRNA and is widely developed in angiogenesis, cell cycle, and so on [15]. It has been reported that down-regulation of miR-130-3p can promote cisplatin resistance in ovarian cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of miR-130a-3p were first studied in mice and were later verified in studies with human embryonic stem cells. It appears to be a vertebrate-specific miRNA and is widely developed in angiogenesis, cell cycle, and so on [15]. It has been reported that down-regulation of miR-130-3p can promote cisplatin resistance in ovarian cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Xiao et al reported that miR130a-3p affects insulin resistance in hepatic cells by targeting the growth factor receptor-bound protein 10 (GRB10), an adapter protein that regulates receptor tyrosine kinase signaling cascades, and confirmed their finding in a mouse model [143]. Mice overexpressing miR-130a-3p had improved glucose clearance, and concomitant over-expression of GRB10 could overcome this beneficial outcome.…”
Section: Micrornas and Insulin Resistancementioning
confidence: 90%
“…A recent study shows that miR-130a-3p is aberrantly reduced in livers of a mouse model with nonalcoholic fibrosing steatohepatitis, and the overexpression of miR-130a-3p inhibits hepatic stellate cells (HSC) activation and proliferation and promotes HSC apoptosis (26). Moreover, miR-130a-3p has been proven regulation of liver steatosis, glucose homeostasis and insulin sensitivity (10,21). miR-301a-3p, as an oncogene, has been reported to be upregulated in several malignant tumors (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are endogenous, noncoding, short, single-stranded RNAs (18-25 nucleotides) that are evolutionarily highly conserved, believed to regulate the translation of target messenger RNAs (mRNAs) by binding to its 3'-untranslated regions (3'-UTRs) and verified to play a role in controlling a variety of biological processes (10). Recently, several studies have highlighted the significance of miRs in maintaining glucose metabolism-associated cell dysfunction (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation